Crystal-to-crystal thermal phase transformation of polymorphs of isomeric 2,3-naphthalene diol ditoluates: mechanism and implications for molecular crystal formation and melting - Tamboli, Majid I.; Krishnaswamy, Shobhana; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Crystal Growth & Design, 2014)
Isomeric para- (1) and meta- (2) ditoluate derivatives of naphthalene 2,3-diol exhibited polymorphism producing three (Forms 1I, 1II, 1III) and two (Forms 2I, 2II) polymorphs each, respectively, depending on the solvent and conditions of crystallization. Crystal forms 1I, 1II, and 2I could be obtained repeatedly, whereas crystal forms 1III and 2II were obtained (separately) in one of the crystallization experiments, each. All the crystal forms were stable at ambient conditions, except for Form 2II, which disintegrated to a powder over 45 days. In contrast, the ortho-ditoluate (3) of naphthalene 2,3-diol did not exhibit polymorphism; it yielded fibrous chiral crystals from different solvents/conditions. Crystal structure analysis of all these polymorphs revealed dominance of energetically similar weak intermolecular interactions such as CH center dot center dot center dot O, CH center dot center dot center dot pi, pi center dot center dot center dot pi, and their interplay in molecular aggregation resulting in polymorphic modifications. Differential scanning calorimetry (DSC), hot stage microscopy, single crystal and powder X-ray diffraction measurements revealed crystal-to-crystal thermal transformation of Forms 1I and 1II crystals to Form 1III crystals and Form 2II crystals to Form 2I crystals. The transformation of Form 1I and Form 1II crystals to Form 1III crystals can be viewed as progressive destabilization of the crystal lattice during heating and converting to metastable phase, whereas the conversion of Form 2II to Form 2I crystals can be considered as reorganization of an unstable crystalline phase to a stable crystalline phase. Hence comparative studies of the structure of stable, metastable, or transient crystals and crystal-to-crystal transformations involving these forms could aid in unraveling the process of crystallization.